On transformative adaptive activation functions in neural networks for gene expression inference - Kunc, Vladimír; Kléma, Jiří (PLoS One, 2021)
Gene expression profiling was made more cost-effective by the NIH LINCS program that profiles only ∼1, 000 selected landmark genes and uses them to reconstruct the whole profile. The D-GEX method employs neural networks to infer the entire profile. However, the original D-GEX can be significantly improved. We propose a novel transformative adaptive activation function that improves the gene expression inference even further and which generalizes several existing adaptive activation functions. Our improved neural network achieves an average mean absolute error of 0.1340, which is a significant improvement over our reimplementation of the original D-GEX, which achieves an average mean absolute error of 0.1637. The proposed transformative adaptive function enables a significantly more accurate reconstruction of the full gene expression profiles with only a small increase in the complexity of the model and its training procedure compared to other methods.
Keywords: Humans; Neural Networks, Computer; Transcriptome; neuronové sítě; Gene Regulatory Networks; výpočetní biologie; genové regulační sítě; Computational Biology; Gene Expression Profiling; transkriptom; lidé; stanovení celkové genové exprese